Menelisik Tradisi Larangan Menikah ”Sekalbu ” Pada Kebudayaan Melayu Koto Baru dalam Perspektif Maqasid Al-Syariah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
Culture and religion often do not go hand in hand due to differences in values and norms, one of these differences can be found in marriage customs. The purpose of this study is to find out how the people of Koto Baru Village view the prohibition of sekalbu marriage. To explain how the influence of the sekalbu marriage tradition according to Koto Baru custom. And how the Maqashid Shari'ah perspective reviews the case of the sekalbu marriage ban. The problem that researchers found in the field is the background of the Koto Baru custom that prohibits sekalbu marriage. Even though there is no single verse or hadith that prohibits the practice of sekalbu marriage. Meanwhile, the Koto Baru custom claims with its saying "Adat basandi syara' syara' basandi kitabullah", so that on the surface it is contrary to Islamic law. This research is a qualitative research using data collection methods, observation, interviews and documentation. The results of research findings in the field that the Koto Baru Community adheres to a matrilineal kinship system. The matrilineal system is a system that regulates the life and order of a society bound in a kinship in the maternal line. Everything is organized according to the mother's lineage. In the customary rules of Koto Baru, a person cannot marry someone who comes from the same family. The prohibition does not invalidate the validity of a marriage because the consequences are not in the form of Islamic legal consequences (sah/bathal, haram) but in the form of social sanctions, namely, being expelled from the customary group because they are considered to have violated customary provisions (banished throughout the custom, ostracized from customary associations and fined).